2010
DOI: 10.1505/ifor.12.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Property Rights, Forest Use and Forest Dependency of Katu Communities in Nam Dong District, Thua Thien Hue Province, Vietnam

Abstract: Sustainable participatory management and conservation requires an understanding of site-specific, rights structure, resource use and resource dependency patterns over time. This paper documents these issues by examining the resource use pattern overtime by the Katu people in Nam Dong district, Thua Thien Hue province, central Vietnam, before and after allocation of natural forest to the households of the community. Household interview, key informant and group discussions were used for data collection and cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…We selected this district because previous studies in the same district focusing on FLA can be used as references. Of 11 communes in the dis- (Thang et al 2010). In particular, after the ban on shifting cultivation in 1997, they settled in the allocated areas and engaged in wet paddy cultivation and horticulture.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…We selected this district because previous studies in the same district focusing on FLA can be used as references. Of 11 communes in the dis- (Thang et al 2010). In particular, after the ban on shifting cultivation in 1997, they settled in the allocated areas and engaged in wet paddy cultivation and horticulture.…”
Section: Study Sitementioning
confidence: 99%
“…Reckless allocation and frequent transfer of allocated land mainly for farming purposes were also reported in a village on the North Central Coast (Nguyen and Sato 2008). One of the latest studies in Nam Dong district criticized that local people's forest use and forest dependency were reduced, even though property rights were enhanced (Thang et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Analogous to valuable timber species, important NTFP which were harvested as whole plants (or substantial plant parts) were therefore largely depleted in HPC-forest. Correspondingly, respondents in a study by Tran et al (2010b) reported that availability of tradeable NTFPs has markedly declined in Nam Đông during the preceding decade (associated incomes have about halved), except for 'broom grass' (Thysanolaema maxima) which prolifically grows in gaps created in forests. Over-exploitation of rattan has become a major problem in the buffer zones of Bạch Mã National Park where new schemes for participative forest protection and resource monitoring have recently been initiated (Ha et al 2016).…”
Section: Ntfps and Associated Values Of Hpc-forestmentioning
confidence: 99%
“…In accordance with expanding cash crops, the collection of wild products has also become more commercialized, with rich households often maintaining controls over collection/trade of key products (McElwee 2008;Sikor and To 2011;Tran et al 2013b). Programs of community-based forest management (CFM) were launched in 2006 and piloted in Nam Đông (Tran et al 2010b), but strong socio-economic dynamics linked to market forces and emerging cash crops outweigh many efforts directed at the conservation and sustainable use of remaining communally managed natural forests. Households in Nam Đông now increasingly use alternative materials to forest products, such as concrete and plastic for house construction, synthetic medicines instead of medicinal plants, and gas for fuel (Tran et al 2013b).…”
Section: Ntfps and Associated Values Of Hpc-forestmentioning
confidence: 99%
“…Some research points at the low quality of the participatory process (Gomiero, Pettenella, Phan Trieu, & Paoletti, ; Castella, Boissau, Hai Thanh, & Novosad, ) and the limited possibilities for local people to access the forests (Dinh & Forestry University Research Team, ; Sunderlin & Huynh, 2005); others put the blame solely on the limited rights and benefits of recipients (Sikor, ; Nguyen, ; Clement & Amezaga, ). Property rights are widely considered the key incentive for local involvement in the policy (Castella, Boissau, Hai Thanh, & Novosad, ; Nguyen, Tran, Sunderlin, & Yasmi, ; Thang, Shivakoti, & Inoue, ). Nevertheless, some case studies observe that exclusive property rights could interfere with customary forest management and give rise to local conflicts (Castella, Boissau, Hai Thanh, & Novosad, ; Sikor & Tran, ).…”
Section: Introductionmentioning
confidence: 99%